Evaluation of Femaxeen® for control of urinary incontinence in women: A randomized, double-blind, placebo-controlled study. (March 2020) - Palacios, Santiago; Ramirez, Marieta; Lilue, Mariella; Vega, Barbara
Highlights: Femaxeen® is a natural product for control of urinary incontinence (UI) in women. This study compared Femaxeen with placebo in women with urge, stress, or mixed urinary incontinence. Femaxeen provided effective control of all three types of urinary incontinence. The safety profile of Femaxeen was similar to that of placebo. Femaxeen is a useful addition to the armamentarium for treating urinary incontinence in women. Abstract: Background and aims: Urinary incontinence (UI) is common in women, with up to 50 % experiencing involuntary loss of urine at some point. Femaxeen®, a formulation containing purified and specific cytoplasmic extracts of pollen, pumpkin seed extract and vitamin E (referred to hereafter as Femaxeen), is indicated for control of UI in women. This study investigated the efficacy and safety of Femaxeen for the prevention and treatment of UI symptoms in women. Methods: In this randomized, double-blind, placebo-controlled trial, 81 women with moderate, severe, or very severe urge (43.4 %), stress (31.6 %) or mixed (25.0 %) UI were allocated to receive Femaxeen or placebo once daily for 90 days. Treatment efficacy was assessed using three validated questionnaires. Findings: Thirty-eight patients per group were analyzed. Femaxeen produced statistically significant improvements from baseline to Day 90 (p < 0.001 for all comparisons) in scores on the International Consultation on Incontinence Questionnaire–Short Form (ICIQ-SF), Measurement of Urinary Handicap (MHU) questionnaire, and Sandvik Incontinence Severity Index. Reduction from baseline in ICIQ-SF and MHU scores at Day 60 and Day 90 was significantly greater with Femaxeen than placebo (p < 0.05 for all comparisons). Femaxeen significantly reduced ICIQ-SF and MHU scores from baseline to Day 60 and Day 90 in all UI types (p < 0.05 for all comparisons except ICIQ-SF scores for stress UI). Femaxeen and placebo were well tolerated. Associated adverse events were few and mild in intensity. Conclusions: Femaxeen is effective for treating UI, and has a safety profile comparable to that of placebo.